Emotional Management in Local Wisdom: Strategies for Enhancing Teachers’ Work Resilience in Pesantren-Based Madrasah - Khoiroh, Ummul; Baharun, Hasan; Abu Hasan Agus; Akmal Mundiri (Al-Qalam Institue, 2025)
This study explores teacher work resilience within the framework of emotional management grounded in pesantren local wisdom at Madrasah Aliyah Nurul Jadid. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, and analyzed with the Miles & Huberman model. The findings reveal four key dimensions strengthening teachers’ resilience. First, individual emotional management is enhanced through self-awareness training, mindfulness, and relaxation techniques, enabling teachers to regulate emotions and foster conducive classroom environments. Second, pesantren values—such as dzikir, sholawat, and the exemplary guidance of kiai—nurture emotional stability, sincere motivation, and a religious work culture. Third, social and organizational support, reflected in halaqah, empathetic leadership, and the tradition of musyawarah, cultivates a harmonious work climate, reduces psychological burden, and reinforces solidarity. Fourth, professional competence development through problem-solving skills and proportional workload management improves both teaching quality and teacher well-being. This study concludes that teacher resilience in pesantren-based madrasahs emerges from the synergy of emotional management, local wisdom, social-organizational support, and professional competence. These findings provide theoretical contributions and practical implications for teacher development in faith-based educational institutions.